PelaksanaanSistemPemiluProporsional MenurutUndang-Undang Nomor 7 Tahun2017 - Ahmatnijar, Dean Antono Putra & Syafri Gunawan & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research is the implementation of the open list proportional electoral system in the City of Padangsidimpuan terms of Uu No. 7 of 2017 concerning Elections. This research is motivated by the role of political parties participating in the elections which was not seen in the 2019 general election.Thisresearch is field research using qualitative descriptive analysis methods. This research data collection method is by means of interviews and documentation with the provisions in Law No. 7 of 2017, which relates to the implementation of the open proportional system of Padangsidimpuan City. The parties examined by the researcher were the Padangsidimpuan KPU and the Padangsidimpuan City legislative candidates.The result states that the implementation of the electoral system using open proportionality has been carried out regarding the determination of seat allocation based on the majority of votes. Its implementation, researcher sees several things that must be evaluated in the legislative election using an open list proportional system. First, the counting of votes using the Saint Legue method is not yet effective and complicated. Second, the intense competition candidate candidates makes the role of political parties invisible. Third, there is a setback in the recruitment pattern of legislative candidates in political parties.